Analisis Rasio Profitabilitas Sebagai Alat untuk Mengukur Kinerja Keuangan pada PT Fast Food Indonesia Tbk yang Terdaftar di Bursa Efek Indonesia - Sarmilania Sarmilania; Pra Gemini; Aminah Aminah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This aims to determine the profitability ratio to measure financial performance at PT Fast Food Indonesia. This research uses quantitative methods and focuses on finding out how Profitability ratios measure financial performance at PT Fast Food Indonesia Tbk from 2019 to 2023. Based on the results of research that has been carried out using profitability ratio calculations, namely Net Profit Margin, Return On Assets, and Return On It is known that Equity at PT Fast Food Indonesia Tbk experiences fluctuations every year except 2023. So it is concluded that the company's financial performance after being calculated using these three indicators is still below the industry average standard except in 2023 capable of being above industry standards.